Newell Ann Van Auken: Spring and Autumn Historiography: Form and Hierarchy in Ancient Chinese Annals - Edward L. Shaughnessy (Asian Studies)
Over the last fifteen years, Newell Ann Van Auken has established herself as the Western world’s foremost authority on the Chunqiu 春秋 (Spring and Autumn), one of China’s traditional five classics. More than that, she is one of the only authorities on the text, or even one of the very few people who has ever read it, at least as an integral text. Most readers encounter it in the course of reading the more entertaining Zuo zhuan 左傳 (Zuo Tradition), or perhaps the Gongyang zhuan 公羊傳 (Gongyang Tradition) or Guliang zhuan 穀梁傳 (Guliang Tradition), its three authoritative commentaries. Van Auken has read the text itself very carefully indeed, so carefully that she has been able to discern formal properties that have escaped even the finest traditional Chinese readers. In her most recent book, Spring and Autumn Historiography: Form and Hierarchy in Ancient Chinese Annals, the sub-title of which is particularly informative, she explores five different aspects of the formal properties of the text to argue that the Spring and Autumn was a conscious attempt to elevate the status of the state of Lu 魯, the state of which it is an annalistic history.